Spatial Distribution and Intensity Analysis of Floods in the Agri-Eleskirt Plain (1955-2017) - Toprak, Ahmet; Sunkar, Murat (Istanbul Univ Press, Istanbul Univ Rectorate, 2019)
In this study, spatial distribution and intensity analyses of torrents and floods in the Agri-Eleskirt Plain over the period of 1955-2017 are conducted. The Agri-Eleskirt plain is an elliptical fertile plain that is surrounded by the Aras Mountains in the north, and it extends in the east-west direction along the Eastern Anatolia Region. Located at an average altitude of 1650 m, this plain is 14-km wide and 40-km long, with an areal coverage exceeding 500 km2. Over the past 20 years, the natural environmental conditions of the river basins draining the plain have deteriorated, increasing the frequency of torrents and floods in this area. The status of floodplains and the settlements in the region, particularly in the city of Agri, has been determined using three types of databases. The Directorate of Disaster Affairs reported 521 flood cases throughout the city of Agri, 159 of which occurred at the plain base. Dividing these data into provincial borders, there were 119 such disasters that occurred in the City Center, 147 in Dogubayazit, 74 in Diyadin, 41 in Taslicay, 7 in Patnos, 46 in Eleskirt, 32 in Tutak, and 55 in the Hamur district. Furthermore, the EM-DAT database reported that the 2007 Agri floods affected 500 people and claimed eight human lives. Finally, the General Directorate of Meteorology reported eight flooding disasters since 1980, indicating the scope of the extraordinary natural disasters that currently occur. Spatial distribution and intensity analyses of these disasters were performed using geographical information systems. Results indicated that the intensity of floods increased toward the south of this region, starting from the entry points of the rivers and moving toward the plain. The frequency, occurrence period, and spatial distribution of the torrents and floods have changed since 1955.
1st Istanbul International Geography Congress -- JUN 20-22, 2019 -- Istanbul, TURKEY
Keywords: Agri-Eleskirt Plain; Torrents and Floods; Spatial Distribution and Intensity Analyses